CNN-Based Automatic Detection of Corn Leaf Diseases Using Desktop GUI Application - Salsabilah, Nisrina Rona; Riadi, Aditya Akbar; Chamid, Ahmad Abdul (STMIK Banjarbaru, 2026)
Early detection of corn leaf diseases plays a crucial role in improving agricultural productivity. This study develops an automatic detection system for corn leaf diseases using a Convolutional Neural Network (CNN) implemented in a desktop-based GUI application. The model was developed using a transfer learning approach with a dataset of 2,400 corn leaf images divided into four classes: Blight, Common Rust, Gray Leaf Spot, and Healthy. The research stages included image preprocessing, model training and evaluation, and implementation of the trained model into an offline desktop application. Experimental results show that the CNN model achieved an accuracy of 90.00%, with precision of 90.02%, recall of 90.00%, and an F1-score of 90.00%. The Healthy class demonstrated the best performance, while the Blight class showed the lowest but remained in a good category. The developed system enables fast, practical, and efficient disease detection and has the potential to support objective early diagnosis in agriculture.Keywords: CNN; Deep Learning; Disease Detection; Corn Leaf; Transfer Learning AbstrakDeteksi dini penyakit daun jagung berperan penting dalam meningkatkan produktivitas pertanian. Penelitian ini mengembangkan sistem deteksi otomatis penyakit daun jagung menggunakan metode Convolutional Neural Network (CNN) berbasis aplikasi GUI desktop. Model dikembangkan dengan pendekatan transfer learning menggunakan 2.400 citra daun jagung yang terbagi dalam empat kelas, yaitu Blight, Common Rust, Gray Leaf Spot, dan Healthy. Tahapan penelitian meliputi preprocessing citra, pelatihan dan evaluasi model, serta implementasi model ke dalam aplikasi desktop yang dapat digunakan tanpa koneksi internet. Hasil pengujian menunjukkan akurasi sebesar 90,00%, precision 90,02%, recall 90,00%, dan F1-score 90,00%. Kelas Healthy memiliki performa terbaik, sedangkan kelas Blight terendah namun tetap dalam kategori baik. Implementasi sistem memungkinkan proses deteksi dilakukan secara cepat, praktis, dan efisien. Sistem yang dikembangkan berpotensi mendukung deteksi penyakit secara objektif serta membantu meningkatkan produktivitas pertanian.Kata kunci: CNN; Deep Learning; Deteksi Penyakit; Daun Jagung; Transfer Learning